Neurological complications of COVID-19: from pathophysiology to rehabilitation. An overview. - Raciti, Loredana; Calabrò, Rocco Salvatore (Acta Biomedica Atenei Parmensis, 2021)
Objective: To evaluate how the SARS-COV2 is able to affect the nervous system, the main neurological manifestation, and the treatment used, including neurorehabilitation.Methods: Studies performed during the current year that fulfilled inclusion criteria were selected from PubMed, Scopus, Cochrane, and Web of Sciences databases. The search combined the terms "Covid 19," "rehabilitation/treatment," and "neurological complications."Results: The exact route by which SARS-CoV-2 can penetrate the CNS is still unknown, although a possible retrograde transynaptic pathway from peripheral nerve endings, and/or through the olfactory bulb, have been suggested. An early management of COVID-19 by a multiprofessional team is fundamental to avoid long term sequaele. Rehabilitation is recommended to improve respiratory and cardiac function, as well as to avoid long term neurological complications.Conclusions: As no specific conclusions in term of prognosis and treatment could be done, research and consensus paper are needed to provide NeuroCovid patients with the best treatment options, including neurorehabilitation.